Control of the metal-to-insulator transition by substrate orientation in nickelates - Peng, Jingjing (2020)
We proved that the critical thickness for metal-to-insulator transition (MIT) of LaNiO3 could be controlled by substrate orientation. By means of density functional theory calculations, films grown on SrTiO3 substrates with (001), (110) and (111) orientations have different amount of charge transfer across the interface. Different charge transfer induces different interfacial conductivity behavior and at the same time modifies the carrier density of adjacent LaNiO3 films. The manipulation of MIT by substrate orientation can be achieved through interfacial charge transfer induced interfacial conductive layer with the modified conductivity of LNO layer.